Biological activity research of male papaya flowers Carica papaya L. on some common cancer cell lines - Ngô Thị Phương Dung; Nguyễn Hoàng Dũng (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
The male papaya tree, Carica papaya L., is widely cultivated in Vietnam, and its flowers possess various pharmacological properties. This study focuses on the biological activities, including antioxidant and anticancer effects, of different fractions extracted from male papaya flowers. Male papaya flowers were extracted using methanol solvent with an extraction efficiency of 15.76%. The recovery efficiencies of the n-hexane, chloroform, ethyl acetate, and water fractions are 11.48, 7.32, 8.05, and 73.15%, respectively. The highest polyphenol content in the water fraction extract is 88.15 ± 1.37 µg GAE/mg extract, corresponding to the best antioxidant activity with an EC50 of 431.10 µg/mL measured by the DPPH method. Using the MTT method, the extract fractions also exhibited cytotoxic activity against HepG2 liver cancer cells, K562 leukemia cells, and B16F10 skin cancer cells. Except for the water extract, which falls outside the tested concentration range (IC50 > 400 µg/mL). The n-hexane fraction extract exhibited strong inhibition against HepG2 cells (IC50 = 196.79 µg/mL), while the chloroform and ethyl acetate fractions showed potent inhibition against K562 cells (IC50 = 83.23 µg/mL and 89.33 µg/mL, respectively). This study is considered an initial exploration in screening and isolating bioactive compounds from male papaya flowers in Dak Lak province, particularly those with cytotoxic activity against cancer cells.